Grammatical versus pragmatic awareness: the case of Egyptian students in an English-medium university - Sorour, Nourhan (AUC Knowledge Fountain, 2015)
Proficiency in a second language (L2) has traditionally been linked to grammatical competence. It has been widely believed that grammaticality is the main indicator of proficiency in a second language. This limited view of L2 proficiency, however, disregards the fact that communicative competence constitutes an integral part of linguistic competence. According to Bardovi-Harlig and Hartford (1991), the development of grammatical competence in L2 usually takes place without the development of the necessary pragmatic competence. This absence of pragmatic competence is one of the major causes of communication breakdowns that may take place between proficient speakers and learners of a language. The purpose of this study is to compare the pragmatic awareness of Egyptian students in an English-medium university to their grammatical awareness in an attempt to determine whether or not there is, in fact, a need for ESL instruction there to focus more on developing ESL learners’ pragmatic awareness. Data were collected from 67 Egyptian ESL learners at two different proficiency levels by means of a judgment task questionnaire adapted from Bardovi-Harlig and Dörnyei’s 1998 study. To supplement the quantitative data, interviews were conducted with four instructors with the aim of gaining insight into their perception of L2 pragmatic awareness. In-group comparisons revealed no significant differences between the grammatical awareness and the pragmatic awareness of the members within each proficiency group. The results of the cross-group comparisons indicated, however, that the high-proficiency group displayed a significantly higher level of grammatical awareness than the low-proficiency group. On the other hand, analysis of the difference in the pragmatic awareness between the high- and low-proficiency groups did not yield any significant results. These findings were not consistent with the results of similar studies carried out earlier in diverse settings where there were apparent and significant differences between the pragmatic and grammatical awareness of learners at different proficiency levels. This inconsistency may be due to the fact that the nature of the context in which this study was conducted is different from the typical EFL and ESL contexts which were examined in previous research. The study was conducted in a university in Egypt where the language of instruction is English rather than in a typical EFL/ESL setting. The importance of the present study lies in that it sheds light on the interrelationship between grammatical and pragmatic awareness in the unique setting of an English-medium university in the heart of Egypt.